2014
DOI: 10.1016/j.stemcr.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Protects Werner Syndrome Lineage-Specific Stem Cells from Premature Aging

Abstract: SummaryWerner syndrome (WS) patients exhibit premature aging predominantly in mesenchyme-derived tissues, but not in neural lineages, a consequence of telomere dysfunction and accelerated senescence. The cause of this lineage-specific aging remains unknown. Here, we document that reprogramming of WS fibroblasts to pluripotency elongated telomere length and prevented telomere dysfunction. To obtain mechanistic insight into the origin of tissue-specific aging, we differentiated iPSCs to mesenchymal stem cells (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 53 publications
6
98
1
Order By: Relevance
“…In Werner syndromes, Bloom syndrome and Rothmund-Thomson syndrome, patients have mutations in the RecQ helicase family of genes, which are important for the re-initiation of stalled replication forks and suppression of inappropriate homologous recombination. Mesenchymal stem cells, but not neural stem cells, reprogrammed from Werner syndrome iPSCs show premature cellular senescence 189 . In Hutchinson-Gilford progeria syndrome, cells accumulate an abnormally processed nuclear intermediate filament called progerin.…”
Section: Dna Damage In Aging Stem Cellsmentioning
confidence: 99%
“…In Werner syndromes, Bloom syndrome and Rothmund-Thomson syndrome, patients have mutations in the RecQ helicase family of genes, which are important for the re-initiation of stalled replication forks and suppression of inappropriate homologous recombination. Mesenchymal stem cells, but not neural stem cells, reprogrammed from Werner syndrome iPSCs show premature cellular senescence 189 . In Hutchinson-Gilford progeria syndrome, cells accumulate an abnormally processed nuclear intermediate filament called progerin.…”
Section: Dna Damage In Aging Stem Cellsmentioning
confidence: 99%
“…Studies of both cross-sectional and longitudinal samples have revealed that, if donor health status and biopsy conditions are controlled, no significant correlation between the age of the donor and replicative life-span of the culture cells can be determined (Holliday, 2014). Additionally, the premature aging process of progeroid fibroblasts (enhanced aging cells) have been demonstrated to share only part of the in vitro aging process of normal fibroblasts (Toda et al, 1998), though recent experimental work showed that telomerase confers protection of accelerated aging in Werner syndrome lineage-specific stem cells (Cheung et al, 2014). Finally, contrary to what expected, CD28– T cells, which exhibit shortened telomeres and markedly decreased proliferative capacity in culture, accumulate with age (Effros, 1998).…”
Section: Theories Of Aging and How They Shape The Definitions Of Smentioning
confidence: 99%
“…However, conflicting evidence (Cheung et al, 2014; Effros, 1998; Holliday, 2014; Toda et al, 1998) and the realization that mice over-expressing telomerase do not live longer (de Magalhães and Toussaint, 2004) are powerful reasons to take pause regarding such therapies. Moreover, telomerase expression has long been linked to promotion of tumor growth and cell proliferation (Peterson et al, 2015), and, therefore, there is the justified fear that the use of telomerase activators may increase cancer development risk.…”
Section: Aging Therapies—cure Aging or Die Trying?mentioning
confidence: 99%
“…For instance, ectopic expression of telomerase results in lifespan extension of WS fibroblasts (Wyllie et al 2000). Reprogramming WS cells to specific lineages that naturally express telomerase also result in lifespan extension as was demonstrated in induced pluripotent and neuronal progenitor cells (Shimamoto et al 2014;Cheung et al 2014). …”
Section: Introductionmentioning
confidence: 91%